Based on HLA-DR?1* allele binding specificities, striking differences in distance and tcr contacting residue orientation can be observed in modified protection-inducing malarial synthetic peptides (2005)
An anti-malarial vaccine is urgently needed, especially against P. falciparum which causes 2 to 3 million deaths each year, mostly in Sub-Saharan African children. This vaccine should contain molecules from the parasites different developmental stages due to the parasites remarkable complexity and genetic variability. The first approach using synthetic peptides from different parasite stage molecules (the SPf66 malaria vaccine) conferred limited protective efficacy in Aotus monkeys and in large field-trials carried out in different parts of the world SPf66 contains red blood cell (RBC) binding merozoite peptides for which immune responses against them are genetically controlled by HLA-DR region. Therefore, a systematic search of conserved high activity binding peptides (HABP) was undertaken aimed at using them as immunogens. However, these peptides were poorly immunogenic and had poor protection-inducing capacity against experimental challenge with a P. falciparum strain highly infective for Aotus monkeys an experimental model with an immune system quite similar to humans. Modifications were thus made to key residues to render them immunogenic and protection-inducing. These native and modified HABPs three-dimensional structure was determined by 1H-NMR studies and their ability in forming stable Major Histocompatibility Class II - peptide (MHCII-peptide) complexes was correlated with their ability to bind in vitro to purified HLA-DR?1* molecules. Our experimental data suggests a correlation between modified HABPs three-dimensional structure, HLA-DR ?1* binding preferences and their protection-inducing capacity in monkeys. Furthermore, the data presented here indicates that a synthetic peptide vaccines three-dimensional structural features dictate both HLA-DR ?1* allele binding preference (imposing genetic restriction on the immune response) and on these vaccines protection-inducing value. Basic knowledge of a parasites functionally active peptides, their 3D structure and their interaction for forming the MHC II- peptide-TCR complex will thus contribute towards designing fully effective multi-component, multi-stage subunit-based malarial vaccines.